Morphological and molecular identification of the Iranian bark and ambrosia beetles (Coleoptera, Curculionidae, Scolytinae) - Amini, Sudabe; Nozari, Jamasb; Smith, Sarah M; Martinez, Isabel; Hosseini, Reza; Faccoli, Massimo (Zootaxa, 2020)
A faunal and molecular taxonomic study of Iranian bark and ambrosia beetle species based on field collections, museum specimens and literature data was carried out from in the period 2011−2016. A total of 29 genera and 84 species were found for Iran. A morphological key for species identification is provided. Molecular identification based on mitochondrial cytochrome c oxidase I (CO1) barcoding region gene was also performed for the collected specimens to confirm morphological identification, and an exclusive DNA barcode was provided and registered for the samples collected in this study. Host plants and distribution of each species in the Palearctic region and in Iran are reported in the key.